Defining Effective Factors on Patients\' Satisfaction Referring to Dental Faculty in Babol University of Medical Sciences: A Principle Step to Socially Accountable Medical Education - Maryam Seyedmajidi; Mina Motallebnejad; Ali Bijani; Moona Sabbagzadeh (Babol University of Medical Sciences, 2013)
ABSTRACT BACKGROUND AND OBJECTIVE: The satisfaction rate of clients toward the offered services qualitatively is the one of the most important indices for the evaluation of services provided in different health and treatment sections. As regards an efficient health system only through the provision of quality services can meet its mission to provide health. This study was done to evaluate the satisfaction rate of patients referred to Dentistry Faculty of Babol University of Medical Sciences, 2010. METHODS: This cross sectional study was done on 500 patients referred to the Babol dental school in 2010 using questionnaires to assess their satisfaction of services. Data were analyzed by T-Test, One way ANOVA, Pearson and Spearmen correlations tests. FINDINGS: In the present study, age and patients' satisfaction of heath care had a direct relationship and satisfaction increased with age (p